PERANAN UNITED NATIONS INTERNATIONAL CHILDREN’S EMERGENCY FUND (UNICEF) DALAM MENANGGULANGI KELAPARAN DAN KEKERASAN PADA ANAK-ANAK DI YAMAN TAHUN 2011-2013 - Frihandy, Rizky; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The journal identifies the role of UNICEF in tackling hunger and violence in children in Yemen in 2011-2013.data technic collection in this study through a multi-case study research library and documents analysis. The writer use theory of the role of International Organizations to describe the role of UNICEF as an International organization dealing with violence and hunger in children Yemen. The writer also makes use of the theory of conflict resolution in view of the root causes of problem conflict which always occurs in Yemen.In an effort to overcome violence and hunger among children in Yemen UNICEF conduct programs as follows, a program of The Peacebuilding, Education and Advocacy in Conflict-Affected Contexts (PBEA), Program kepeduliaan of the right child (Evidence for children's rights), and Program Empowerment children's rights (Empowerment for children's rights). While tackling hunger for children in Yemen UNICEF Humanitarian action running programs for children.Keywords: UNICEF, hunger and child abuse, Conflict, Theory of International Organization, Theory of Conflict Resolution.